EFECTO EN EL CRECIMIENTO Y PRODUCCIÓN DE AJÍ TABASCO (Capsicum frutescens) CON LA BIOFERTILIZACIÓN DEL ALGA MARINA (Ascophyllum nodosum) - VILLAVICENCIO VILLACIS, MANUEL ALEXANDER (2023)
The objective of this research is to evaluate the effects of the application of biostimulant based on the seaweed Ascophyllum nodosum on the growth and production of Tabasco Chili Pepper (Capsicum frutescens), at the “La María” University Campus. Using a Completely Randomized Design (DCA), with five treatments and four repetitions, the treatments used were a concentration of the biofertilizer based on the algae A. nodosum as follows: T0-0%, T1-100%, T2-75%, T3-50% and T4-25%, whose measurements were compared using the 95% Tukey test. The research was divided into two trials: the first studied the growth of chili during the initial stage in the greenhouse, the main result was that T4-25% produced seedlings with higher AP after 30 days, after having germinated with 4.75 cm, also reaching a LH and DH of 3.15 cm and 2.61 cm, while T1-100%, achieving seedlings with a LR greater than 5 cm; In the second trial, it was based on growth and production at the field level, where it was evident that T4-25%, achieving a greater AP at 30, 60 and 90 days after transplanting with 19.08 cm. 80.55 cm and 119.51 cm, also recorded a greater NF of 102.66 per plant, which obtained a LF and DF of 4.61 cm and 1.28 cm, a greater PF of 7.36 g, thus acquiring a BFF and BSF of 276.41 g and 23.56 g, increasing the yield of the crop with 6300.48 kg/ha. In addition, this treatment generated the highest net profit of $3238.51 per hectare, with the A. nodosum algae being a sustainable alternative to optimize the vegetative and productive development of the Tabasco pepper crop.